Dyadic Coping of Kidney Transplant Recipients and Their Partners: Sex and Role Differences - Tkachenko, Daria; Franke, Laura; Peters, Luisa; Schiffer, Mario; Zimmermann, Tanja (Frontiers in Psychology, 2019)
Background: Coping with stressful health issues – e.g. organ transplantation – can affect interpersonal relationships. Objective: The study examines individual and dyadic coping (DC) in kidney transplant recipients and their partners under consideration of sex and role differences. The Dyadic Coping Inventory allows analyzing partners’ perception of their own DC and also of their partner’s behavior and investigating different perspectives with three discrepancy indexes (similarity, perceived similarity, congruence). Methods: Fifty-six kidney transplant recipients and their partners completed self-report questionnaires (N=112) on DC, depression, anxiety and relationship satisfaction Average age of patients was 58.1 years and of partners 57.2 years; 64.3% of the patients were male; time since transplantation was on average 9.7 years. Results: (1) Individual and dyadic functioning: In couples with male patients female caregivers showed higher own supportive DC than the males. In couples with female patients, women reported higher own stress communication, supportive DC, total positive DC and total DC as well as depression compared to men. (2) Regarding the discrepancy indexes, in couples with male patients worse similarity in DC reactions of the couple was associated with higher depression of males as well as higher anxiety of females. Moreover, lower comparability of own DC with partner-perception was correlated with higher depression in males. In couples with female patients, higher comparability was associated with higher DC. Higher DC of males was associated with lower own anxiety and better similarity in DC reactions. Worse similarity of male spouses showed correlations with higher depression and anxiety of females. (3) Sex and role differences occurred. No significant differences between male patients and male partners occurred whereas female patients showed higher own stress communication, supportive DC, common DC, total positive DC, total DC and relationship satisfaction compared to female caregivers (role differences). The same differences were found comparing female with male patients. No differences occurred between male and female caregivers (sex differences). (4) Regarding relationship quality, DC and similarity index seem to be important predictors. Discussion: Results demonstrate the relevance of DC in couples with kidney transplantation and show differences between males and females as well as patients and partners.